Working Stiffs, Union Maids, Reds, and Riffraff : An Expanded Guide to Films about Labor - Zaniello, Tom, 1943- (Book collections on Project MUSE., 2003)
Publisher description: The revised and expanded edition of Working Stiffs, Union Maids, Reds, and Riffraff offers 350 titles compared to the original edition's 150. The new book is global in scope, with examples of labor films from around the world. Each entry includes a critical commentary, production data, cast list, MPAA rating (if any), suggested related films, annotated references to books and websites for further reading, and information about availability of films for rental and/or purchase. This edition addresses both historical and contemporary films and features many more documentaries and hard-to-find information about agitprop and union-financed films. Two new sections will help the reader discover labor films in chronological order or by nationality or affiliation with certain cinematic movements.